(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2026)
Tanjung Api-Api Port connects South Sumatra Province and Bangka Belitung Islands Province. A total of 15 ships divided into seven trips per day cross the Bangka Strait. Sea transportation is more popular among passengers because it is cheaper than air transportation. Forecasting passenger growth is necessary as a basis for improving passenger services. The forecasting method used is the Exponential Smoothing method, as passenger data over the past five years at Tanjung Api-Api Port shows a seasonal trend. The historical data used is passenger departure and arrival data. The results of the analysis show that departure passenger data is modelled using the Simple Seasonal model, while arrival passenger data is modelled using the Winter Additive model. The departure passenger data forecast shows a stable and consistent trend without any major spikes as in the previous period. Meanwhile, the arrival passenger data forecast shows a gradual and upward trend. The accuracy of the model obtained for forecasting departure passenger data was 76.5%, and the accuracy of the model for forecasting arrival passenger data was 81.86%. With the accuracy of the model obtained, passenger growth forecasts can be used as a reference for policies in managing facilities at Tanjung Api-Api Port.